HALAL INDUSTRIAL PARK: INOVASI KAWASAN GREEN ECONOMY DALAM PEMBERDAYAAN INDUSTRI KECIL DAN MENENGAH - Nuryanti; Hak, Muhamad Bai'ul; Singandaru, Adhitya Bagus (Elastisitas : Jurnal Ekonomi Pembangunan, 2024)
This research aims to explain the innovation of Governor Regulation No. 6 of 2022 on Roadmap of West Nusa Tenggara Halal Industrial Park. The research used integrated literature approach which are the combination between literature review and systematic review. This method used to explain the concept of the Roadmap of Halal Industrial Park in terms of the Green Economy perspective and the empowerment of Small and Medium Industries (SMI) in Wes Nusa Tenggara Province. The results show that the Roadmap of Halal Industrial Park is a clean and clear green location that functioned for scaling up and increasing productivity of SMI. The Roadmap of Halal Industrial Park ensures the sustainability of raw materials for industry through integrated urban farming. This regulation also assures the empowerment of SMI from the production process to market segmentation. Furthermore, the SMI will be encouraged to produce national and international product standards.